Desarrollo de un prototipo de sistema de limpieza de piezas mecánicas por ultrasonido y controlado mediante visión artificial para el "Comercial el Reciclador" - Bravo Ojeda, Milton Vinicio (2018)
The purpose of this technical project is to design and implement a prototype machine that allows the cleaning of recyclable mechanical parts by means of the use of ultrasound and verification through the artificial vision for the Commercial Company the Recycler. The prototype allows the elimination of dirt such as dust, burned oil, grease, among others. Of the recycled mechanical parts existing in the Commercial Company the Recycler stories such as pinions, bearings, pulleys, horns, among others. By using a biodegradable chemical DLM-101 of high concentration, it is easy to remove the greases adhered to the aforementioned parts. The ultrasound used for the washing whose operation is given by ultrasonic cavitation, which allows the substances and the microscopic level to be deposited in these pieces. The prototype uses artificial vision in the analysis of the image to verify the reduction of dirt in the mechanical parts that are reusable and for possible commercialization.